Living for the future theological ethics for coming generations - Muers, Rachel (London ; New York : T & T Clark, 2008)
Our relationship to future generations raises fundamental issues for ethical thought, to which a Christian theological response is both possible and significant. A relationship to future generations is implicitly central to many of today's most public controversies - over environmental protection, genetic research, and the purpose of education, to name but a few; but it has received little explicit or extended consideration. In Living for the Future Rachel Muers argues and seeks to demonstrate that to consider future generations as ethically significant is not simply to extend an existing ethi
Acknowledgements; Introduction; 1 Beginning with the Revolution; 2 Searching the Scriptures; 3 Idolatry and Intergenerational Relations; 4 Being Called into Communities; 5 Being in Someone Else's Place; 6 Mothering the Future; 7 Sustainable Thinking; 8 Passing on the Genes; Afterword; Bibliography; Index; Biblical References
Includes bibliographical references (p. 201-210) and index.
Description based on print version record.
Keywords: Christian ethics; Intergenerational relations -- Religious aspects -- Christianity; Religion; RELIGION -- Christian Theology -- Ethics; Theologische Ethik; Prognose; Electronic books